An analysis of an underwater turn for butterfly and breaststroke - Kishimoto, T.; Takeda, T.; Sugimoto, S.; Tsubakimoto, S.; Takagi, H. (Biomechanics and Medicine in Swimming XI, 2010)
The purpose of this study was to analyze selected characteristics of the "Apnea Turn", a new underwater turn and to compare this turn with the conventional "Open Turn". The subjects were ten elite competitive butterflyers and breast strokers. The 5 m Round Trip Time (5 m-RTT) of the Apnea turn was faster than the Open turn (5.55±0.27 s and 5.62±0.33 s). While the times of the into turn phase and out of turn phase of 5 m-RTT for the Apnea turn were faster than the Open turn, the time of the pivot phase was significantly slower than the Open turn. The push off velocity of the Apnea turn was significantly higher than the Open turn (3.02±0.11 m·s-1 vs 2.92±0.06 m·s-1). These results suggest that the Apnea turn may improve swimming performance and may be a prospective new turning method.